The Effect of Vocabulary Mastery on Students’ Reading Comprehension - Nur Rahmah; Muh. Tahir; Ahmad Talib (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to decide the impact of vocabulary mastery on the reading comprehension of junior high school students. This study utilized a quantitative strategy with simple linear regression analysis. This research data was collected through a test consisting of vocabulary mastery and reading comprehension. The sample of the research was determined using random sampling. There are 59 students from SMP Negeri 2 Pangkajene and 16 students from SMP Negeri 4 Pangkajene. The aftereffects of this study show that there is an impact of vocabulary mastery on students’ reading comprehension. It is clear from the consequences of the computation of the correlation (R) is 0.573 with a coefficient of determination (R Square) of 0.329 which infers that the impact of the independent variable (vocabulary mastery) on the dependent variable (reading comprehension) was 32.9%. This shows that i 0.000 < 0.05. The conclusion is (Ho) is dismissed and (Ha) is acknowledged.